ANALISIS PERBANDINGAN LAPORAN KEUANGAN LABA RUGI PT. PELINDO REGIONAL 1 - Amelia Siregar, Cyntia; Samri Juliati Nasution, Yenni (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STIE Pontianak, 2023)
Pelindo 1 Provincial North Sumatra was the target of this study. This study aims to investigate and clarify the origins of financial statements as well as the variables affecting PT's profitability and income. Geographical Pelindo 1. The hypothesis concerning the relationship between financial summaries of benefit and loss and benefit and loss on organization is the one used in this investigation. This study employed a quantitative approach. PT. Pelindo Territorial 1 benefit and misfortune budget report data from the previous 2 (two) years' worth of research. This study uses flat examination for information analysis. According to level analysis results, net gain increased by (11.8%) in 2020–2021, while working pay increased by (636.4%) over the previous year. Profit after tax and total profit both grew by 1,359.2% in the current year. Given that the effects of the global Coronavirus pandemic are still being felt, as well as a flawed model that upsets the standard method of handling import containers, there will be a decrease in benefits organization in 2020. As a result, certain regions and countries won't be able to receive deliveries as expected due to lockdown.